ANTIHYPERGLYCEMIC EFFECTS OF THYMOQUINONE IN DIABETIC RATS - Jabbar A.A. Al-Sa; Hashim M.A. Kareem; aidi; Wijdan T.M. Al-Tameemi (Basrah Journal of Veterinary Research)
To investigate the antihyperglycemic potent of thymoquinone (TQ), this study has been conducted in streptozotocin-induced diabetic male rats.Diabetes was induced by single injection with streptozotocin (60 mg/kg b.w., i.p.). Rat ≥ 200 mg/dl of blood glucose was used as diabetic.Sixty five adult male rats (aged 56 days and weighted 138±8.8g) were divided into five groups, non-diabetic control (were drenched with drinking water) and four diabetic groups(DM, TQ50,TQ100, and DMI) were drenched with drinking water,TQ (50 mg/kg, bw), TQ (100 mg/kg, bw), and injected with insulin (4 IU/animal), respectively, for 42 days. During the experiment,body weight gains were recorded and blood samples were obtained weekly for assessment of plasma glucose and insulin concentrations. TQ treated male rats showed normal activity and body health throughout the experiment. Significant decrease of body weight gain has been recorded in untreated diabetic (DM) and insulin treated diabetic (DMI) groups as compared with that of intact control (C) and TQ treated diabetic (TQ50 and TQ100) groups, started from the fourth day of experiment, while DM group registered the lowest body weight gain among the experimental groups. Results of blood glucose concentrations referred to significant elevation in diabetic groups as compared with intact control. While in comparison between the diabetic groups, blood glucose concentration decreased significantly TQ50, TQ100, and DMI groups compared with DMI group. It has been found that insulin treated (DMI) and TQ treated (TQ50 and TQ100) male rats recorded no significant difference in serum insulin concentration when compared with each other but they were significantly lower than that of intact control male rats (C), but the average means of these four groups were significantly higher than that of non-treated diabetic male rats (DM).These changes were time dependent during the studied experimental period. It can be concluded that drenching of 100 mg/kg of TQ has potent hypoglycemic effect in experimentally-induced diabetic male rats.